GENETIC SOURCES AND TECTONOPHYSICAL REGULARITIES OF DIVISIBILITY OF THE LITHOSPHERE INTO BLOCKS OF VARIOUS RANKS AT DIFFERENT STAGES OF ITS FORMATION: TECTONOPHYSICAL ANALYSIS - Semen I. Sherman (Геодинамика и тектонофизика)
The paper presents the first tectonophysical reconstruction of initial divisibility of the protolithosphere as a result of convection in the cooling primitive mantle. Initial division of the protolithosphere into separate masses, i.e. prototypes of the blocks, and their size are predetermined by the emerging Rayleigh-Benard convection cells. In studies of geology and geodynamics, the Rayleigh-Benard convection cells were first referred to as a factor to explain the formation of initial continental cores. Considering the Rayleigh-Benard cells and their structural relics can help clarify initial divisibility of the protolithosphere and the origin of the major lithospheric plates, i.e. prototypes of continents. In our opinion, the initial mega-scale block structure of the protolithosphere and the emerging lithosphere were predetermined by the Rayleigh-Benard cells as they were preserved in the emerging lithosphere and their lower boundaries corresponded to the core-mantle boundary, i.e. one of the major discontinuities of the planet. Our theoretical estimations are in good agreement with the number and sizes of the Earth's theorized first supercontinents, Vaalbara and Ur. In our tectonophysical discussion of the formation of the lithospheric block structure, we analyze in detail the map of modern lithospheric plates [Bird, 2003] in combination with the materials from [Sherman et al., 2000]. In the hierarchy of the blocks comprising the contemporary lithosphere, which sizes are widely variable, two groups of blocks are clearly distinguished. The first group includes megablocks with the average geometric size above 6500 km. Their formation is related to convection in the Earth mantle at the present stage of the geodynamic evolution of the Earth, as well as at all the previous stages, including the earliest one, when the protolithosphere emerged. The second group includes medium-sized blocks with the average geometric size of less than 4500 km and those with minimum sizes, such as rock lumps. They reflect primarily the degradation of megablocks as a result of their destruction due to high stresses in excess of the tensile strength of the medium. This group may also include blocks which formation is related to convection in the upper mantle layer, asthenosphere. There are grounds to assume that through the vast intermediate interval of geologic time, including supercycles of Kenorlend, Rodin, and and partically Pangea, the formation of the large lithospheric blocks was controlled by convection, and later on, they were 'fragmented' under the physical laws of destruction of solid bodies. However, it is difficult to clearly distinguish between the processes that predetermine the hierarchy of formation of the block structures of various origins – sizes of ancient lithospheric blocks cannot be estimated unambiguously.Thus, mantle convection is a genetic endogenous source of initial divisibility of the cooling upper cover of the Earth and megablock divisibility of the lithosphere in the subsequent and recent geodynamic development stages. At the present stage, regular patterns of the lithospheric block divisibility of various scales are observed at all the hierarchic levels. The areas of the lithospheric megaplates result from regular changes of convective processes in the mantle, which influenced the formation of plates and plate kinematics. Fragmentation of the megaplates into smaller ones is a result of destruction of the solid lithosphere under the physical laws of destruction of solid bodies under the impact of high stresses.